Synthesis of Graphene@C3N4-Cu Beads Nanocomposites and their Antimicrobial Efficacy Against Drug-Resistant Bacteria and Fungi - Khan, Mohd Sajjad Ahmad (Pharmaceutical Nanotechnology, 2025)
BackgroundIncreased intake of drugs worldwide and the subsequent advent of resistance to existing antibiotics have globally threatened health organizations. To combat the problem of these drug-resistant infections, as an alternative approach, graphene (GN)-related nanomaterials have attracted significant interest because of their effective anti-microbial potential. The present study shows the synthesis and characterization of nanocomposite of GN with carbon nitride viz. g-C3N4, g-C3N4-Cu, and GN@g-C3N4-Cu. Further, we investigated the anti-microbial potential of these nanocomposites against strains of Gram-negative and Gram-positive bacteria, viz., a multidrug-resistant strain of Pseudomonas aeruginosa (MDRPA), a methicillin-resistant strain of Staphylococcus aureus ATCC33593 (MRSA), and an azole-sensitive fungal strain (Candida albicans ATCC14053).MethodsThe morphological characterization of GN@g-C3N4-Cu nanocomposite was executed by scanning electron microscopy, whereas the elemental analysis and their distribution were studied by energy-dispersive X-ray spectroscopy and elemental mapping methods. Furthermore, the anti-microbial and antibiofilm efficacies of g-C3N4, g-C3N4-Cu, and GN@g-C3N4-Cu nanocomposites were evaluated by disc diffusion, two-fold serial micro broth dilution, and 96 well microtiter plate methods.ResultsThe ternary g-C3N4-Cu@GN, apart from the structures of g-C3N4-Cu, showed big sheets of GN. The observance of C, N, O, and Cu in the elemental analysis, as well as their uniform distribution in the mapping, indicated the successful fabrication of g-C3N4-Cu@GN. GN@g-C3N4-Cu followed by g-C3N4-Cu and (g-C3N4) exhibited significantly higher antimicrobial activity (zone of inhibition from 14.33 to 49.33 mm) against both the drug-resistant bacterial strains and azole-sensitive C. albicans. MICs of nanocomposites ranged from 32 -256 µg/ml against the tested strains. Whereas all three nanocomposites at sub-MICs (0.25 A- and 0.5 A- MICs) showed concentration-dependent inhibition of biofilm formation in MDRPA, MRSA, and C. albicans by allowing 11.35% to 32.59% biofilm formation.ConclusionOur study highlights the enhanced efficiency of GN@g-C3N4-Cu nanocomposites as potential anti-microbial and antibiofilm agents to overcome the challenges of multi-drug-resistant bacteria and azole-sensitive fungi. Such kind of nanocomposites could be used to prevent nosocomial infections if coated on medical devices and food manufacturing instruments.
Keywords: Antibiofilm